Enhanced Postsurgical Cancer Treatment Using Methacrylated Glycol Chitosan Hydrogel for Sustained DNA/Doxorubicin Delivery and Immunotherapy - Seo, Hee Seung; Han, Jun-Hyeok; Lim, Jaesung; Bae, Ga-Hyun; Byun, Min Ji; Wang, Chi-Pin James; Han, Jieun; Park, Juwon; Park, Hee Ho; Shin, Mikyung; Park, Tae-Eun; Kim, Tae-Hyung; et al. (Biomaterials research, 2024)
Background: Cancer recurrence and metastasis are major contributors to treatment failure following tumor resection surgery. We developed a novel implantable drug delivery system utilizing glycol chitosan to address these issues. Glycol chitosan is a natural adjuvant, inducing dendritic cell activation to promote T helper 1 cell immune responses, macrophage activation, and cytokine production. Effective antigen production by dendritic cells initiates T-cell-mediated immune responses, aiding tumor growth control. Methods: In this study, we fabricated multifunctional methacrylated glycol chitosan (MGC) hydrogels with extended release of DNA/doxorubicin (DOX) complex for cancer immunotherapy. We constructed the resection model of breast cancer to verify the anticancer effects of MGC hydrogel with DNA/DOX complex. Results: This study demonstrated the potential of MGC hydrogel with extended release of DNA/DOX complex for local and efficient cancer therapy. The MGC hydrogel was implanted directly into the surgical site after tumor resection, activating tumor-related immune cells both locally and over a prolonged period of time through immune-reactive molecules. Conclusions: The MGC hydrogel effectively suppressed tumor recurrence and metastasis while enhancing immunotherapeutic efficacy and minimizing side effects. This biomaterial-based drug delivery system, combined with cancer immunotherapy, can substantial improve treatment outcomes and patient prognosis.